Inheritance of male sterility in apricot - Burgos, L.; Egea, J. (International Journal of Horticultural Science, 2001)
Progenies (total of 1,114 seedlings) from crosses representing all possible genotypic combinations between 4 male-fertile and 1 male-sterile apricot parents were scored for the male sterility trait. Crosses between putative heterozygous normal cultivars yielded 25% of male-sterile seedlings, which supports a previous hypothesis that male sterility is controlled by a recessive allele of one nuclear locus. Crosses between those parents and putative homozygous normal cultivars did not produce any male-sterile tree. Finally, the proportion of male-sterile progeny in crosses between a male-sterile and two male-fertile cultivars depended on the genotype of the male parent. When it was heterozygous approximately 50% of the progeny was sterile, whereas when a homozygous fertile parent was used, no male-sterile progeny was obtained. These results confirm a previously proposed model, in which the male sterility trait in apricot is controlled by a single recessive gene.